Self-medication practices with antibiotics among Chinese university students. (January 2016) - Zhu, X.; Pan, H.; Yang, Z.; Cui, B.; Zhang, D.; Ba-Thein, W.
Abstract: Objectives: Self-medication with antibiotics (SMA) is a serious global health problem. We sought to investigate SMA behaviors and risk factors among Chinese university students, and further explore the association between SMA practices and adverse drug events (ADEs). Study design: Cross-sectional study. Methods: An online survey was conducted at Jiangsu University (JSU) in eastern China in July 2011 using a pretested questionnaire. Results: Out of 2608 website visitors, 1086 participated in the survey (response rate: 41.6%), 426 respondents were excluded for not being a JSU student or repeat participation, 660 (2.2% of JSU students) were included in analysis, and 316 students (47.9%) had a lifetime history of SMA. Among self-treated students, 43.5% believed that antibiotic was suitable for viral infections, 65.9% had more than one SMA episode in the previous year, 73.5% self-medicated with at least two different antibiotics, 57.1% and 64.4% changed antibiotic dosage and antibiotics during the course, respectively. Female gender, older age, and prior knowledge of antibiotics (PKA) were identified as independent risk factors of SMA. There was no difference between students with and without PKA regarding SMA frequency, use of polyantibiotics, and switching antibiotic dosage or antibiotics. ADEs happened to 13.3% of self-medicated students. Frequent change of dosage and simultaneous use of the same antibiotic with different names were independent risk practices associated with an ADE. Conclusions: Our findings substantiate high SMA prevalence among Chinese university students. Older age and PKA are independent SMA risk factors common to Chinese university students and female gender is exclusive SMA risk factor for JSU students. Poor SMA practices are associated with ADEs. Strict regulations on antibiotic sales and public education reinforced by further health care reform are recommended. Highlights: Self-medication with antibiotics among Chinese university students is highly prevalent. Female gender, older age, and prior knowledge of antibiotics are independent risk factors. Poor self-medication practices are positively associated with adverse drug events. Strict regulations on non-prescription antibiotics are recommended.